Hapusnya Hak Tagih Pemegang Obligasi Lama Terhadap Negara Ditinjau dari UU Perbendaharaan Indonesia / Indische Comptabiliteitswet (ICW) - Nizar Yudhistira; Yuli Indrawati (LPPM Universitas Ekasakti Padang, 2023)
Old bonds issued post-Indonesian independence (1950, 1959, and 1964) remain a persistent issue. Some bondholders believe they can demand repayment from the government through lawsuits. This research assesses old bondholders' claim rights under the Indonesian Treasury Law (Indische Comptabiliteitswet - ICW). Using a doctrinal research approach and juridical methods, this research examines the contractual relationship between bondholders and the government, based on mutual agreement. Obligations can expire due to time limitations (extinctive prescription), as stipulated in Article 1381 of the Civil Code. Article 60 of the ICW specifies a 5-year limit to claims against the state, beginning from the year of debt. Since the old bondholders took no action within the 5-year window from 1978 to 1983, their right to demand payment from the government has lapsed due to extinctive prescription. Consequently, the government is no longer obligated to pay the old bondholders. This research underscores the significance of understanding legal time constraints in contractual relationships.